Perupa: Nashar - Gesyada Annisa Namora Siregar (JSRW (Jurnal Senirupa Warna), 2017)
Abstrak: Tiga-¬Non: non-¬prakonsepsi, non¬-teknik akademis, dan non-¬estetik akademis adalah gagasan yang dikemukakan seniman dan pemikir seni rupa Indonesia, Nashar, pada tahun 1970-an. Tulisan ini merupakan rangkuman proses untuk memahami perjalanan Nashar menemukan Tiga-Non, pengaruh kawan dan gurunya, Oesman Effendi dan Affandi dalam sikap kepelukisannya, apa yang dimaksudkan Nashar dengan Tiga-Non-nya, dan terakhir melihat bagaimana Tiga-¬Non dipraktikkan oleh Nashar dalam karya-karyanya. Abstract: Non-preconception, non-academic technique, and non-academic esthetic are the three concepts presented by Nashar, one of the Indonesian fine arts artists and thinkers, in 1970s. This article is a summary covering the process of understanding Nashar’s journey to find his Three-Non, the influence of a friend cum teachers, Oesman Effendi and Affandi in his attitude to his painting career, what he meant with his Three-Non, and lastly, to see how the Three-Non was operated by Nashar in his works.